2018
DOI: 10.1177/000313481808400528
|View full text |Cite
|
Sign up to set email alerts
|

An Age-Based Analysis of Pediatric Melanoma: Staging, Surgery, and Mortality in the Surveillance, Epidemiology, and End Results Database

Abstract: The pediatric melanoma population is not well described, and current guidelines for their management are not well defined. Our study aims to identify this population, treatment modalities, and outcomes using a national population-based database. We reviewed the Surveillance, Epidemiology, and End Results database (2004–2008). Patients ≤21 years old with melanoma were included and grouped into ≤12 years of age, 13 to 18 years, and 19 to 21 years. Clinical characteristics were analyzed across the groups. A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 27 publications
3
9
1
Order By: Relevance
“…Similar trends have been observed in previous studies. 2,5,8,[12][13][14][15][16] However, our results differ from a previous international cancer registry analysis which found that males made up a greater percentage of cases before the age of 10, while females made up a greater percentage of cases after the age of 10. 8,13 Our results demonstrated a greater burden of melanoma in males age 13-15 and females age 16-17.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Similar trends have been observed in previous studies. 2,5,8,[12][13][14][15][16] However, our results differ from a previous international cancer registry analysis which found that males made up a greater percentage of cases before the age of 10, while females made up a greater percentage of cases after the age of 10. 8,13 Our results demonstrated a greater burden of melanoma in males age 13-15 and females age 16-17.…”
Section: Discussioncontrasting
confidence: 99%
“…2,5,12,13,15,16 Other studies have also identified Hispanics as the group second most likely to develop pediatric melanoma after Whites. 4,15,16 By anatomic location, the most frequent presenting site was the trunk, while the least frequent site was the upper extremities and head/neck. Our findings are comparable to other studies which observed pediatric melanomas most often present on the trunk or lower extremities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultimately, 44 studies met our inclusion criteria and were included in this systematic review ( Supplemental Figure S1 ). 2 , 4 , 6 , 10 , 14 - 53…”
Section: Resultsmentioning
confidence: 99%
“…Five studies reported AJCC cancer stages for black patients, with weighted mean % of patients at stage I ( n = 501 patients, 52.6%) , stage II ( n = 223, 24.1%), stage III ( n = 123, 16.3%), and stage IV ( n = 101, 13.2%). 4 , 6 , 15 , 19 , 33 Seven studies comparing non-Hispanic white and black survival reported histological subtype stratified by race, with total patients and mean proportion of patients as follows: nodular melanoma (black: n = 1090, 10.0%; non-Hispanic white: n = 72029, 9.1%), lentigo maligna melanoma ( n = 196, 3.7%; n = 75631, 7.6%), superficial spreading melanoma ( n = 1611, 19.0%; n = 312754, 39.3%), and acral lentiginous melanoma ( n = 2107, 19.4%; n = 8141, 0.99%). 2 , 4 , 6 , 18 , 23 , 34 , 45 The most common subtype reported in black patients were superficial spreading melanoma in 4 studies, and acral lentiginous melanoma in 3 studies, while superficial spreading melanoma was the most commonly reported subtype for non-Hispanic white patients among all 7 studies.…”
Section: Resultsmentioning
confidence: 99%